Theoretical and practical methods in process of artwork creation-analyzing personal poetics of ornament - Žderić, Tamara D. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2018)
The subject of this article is ornament and its role in the author’s artwork observed through the methodology of work’s creation. Ornament is “the oldest form of higher mathematics“. The period to which this research refers is the process of creation of my doctoral art project, but it also refers to the period immediately preceding it, and which contains my initial steps in the field of fine art and the first signs of may own use of ornamentics. Therefore, the task of this paper is to provide some answers with regard to the methods and their use in creating of an author’s work of art. It also provides answers with regard to how interaction of methods affects the shaping of artistic experience, which are in this case  defined by the notion of ornament. Research methodology refers both to the theoretical and the practical part. The goal of this paper is to observe and refer to the process of the artwork creation, which is deeply personally determined, but through the prism of both theory and practice. s. . Another focus point of this text is to prove  that every work of art is the subject of examination by the author despite the conventional and widespread opinion that it emerges automatically and as an explicit and unique  product of emotions. Thorough research done on author’s own work lead to the following results standing out in this review: A. Every procedure used in the process of creating an artwork is determined by ratio (it is made under the strict control of the mind) and emotions (intuitively). 2. It is possible to systematically disintegrate and analyze the potential meanings of personal ornamentics and symbolic  layersdefining it by applying theoretical and practical methods. 3.  By applying the method, the work of art becomes demonstrable.
Keywords: methods; emotions; sense; art; ornament